Mobile web for student portal based on mobile information architecture / Syed Mohammad Hafiz Syed Shahrul Zaman - Syed Shahrul Zaman, Syed Mohammad Hafiz (2012)
Due to mobile phone limitation, the small screen size of the device cannot cater to display lots of information in UiTM Student Portal as it would do in bigger screen size of laptop. The limitation causing difficulty and complexity while navigating using the mobile phone. As a result, the navigation ends in user frustration. The goal of this project is to adopting mobile information architecture that will solve the mobile phone information display limitation issues. A good mobile website needs to be simple in its information architecture. To keep it simple, the website's defined goal was obtained from the interview session with the web developer, while the context of use and most used application were obtained by questionnaire distributed. Related mobile websites also ware surveyed to outline the mobile information architecture. Several tools such as sitemap, clickstream, wireframe and prototype were constructed to assist in developing simpler information architecture. To determine whether the recommend mobile website developed that adopting the mobile information architecture meets the usability, a usability testing session was conducted. System Usability Scale (SUS) was used for the usability testing. The usability testing result shows that, a big marginal difference in usability scores between the current interface of Student Portal in mobile phone and the recommended website developed where the users preferring the Student Portal in mobile phone that adopting the mobile information architecture. In conclusion, the mobile information architecture eases the user to navigate the mobile website better and less frustration. The aim of the project is achieved.